2017
DOI: 10.1017/s0007485317000852
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in host utilization by two host-associated populations ofAphis gossypiiGlover

Abstract: Biological and morphological plasticity in polyphagous insect herbivores allow them to exploit diverse host plant species. Geographical differences in resource availability can lead to preferential host exploitation and result in inconsistent host specialization. Biological and molecular data provide insights into specialization and plasticity of such herbivore populations. In agricultural landscapes, Aphis gossypii encounters several crop and non-crop hosts, which exist in temporal and spatial proximity. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…As an example of geography related differentiation in hemipteran insects in another continent, high COI genetic distances (highest 4.7%) were observed between populations of stink bug Chinavia hilaris from the west coast and east coast of the United States and indicated that geographical isolation may promote cryptic diversity [82]. However, population differentiation of phytophagous insects may be driven simultaneously by both host plant and geography factors, as discussed in some previous cases [106,107]. Thus, more detailed studies on the differentiation of subtropical aphid populations at fine scales are needed in the future.…”
Section: Discussionmentioning
confidence: 83%
“…As an example of geography related differentiation in hemipteran insects in another continent, high COI genetic distances (highest 4.7%) were observed between populations of stink bug Chinavia hilaris from the west coast and east coast of the United States and indicated that geographical isolation may promote cryptic diversity [82]. However, population differentiation of phytophagous insects may be driven simultaneously by both host plant and geography factors, as discussed in some previous cases [106,107]. Thus, more detailed studies on the differentiation of subtropical aphid populations at fine scales are needed in the future.…”
Section: Discussionmentioning
confidence: 83%
“…When the temperature is higher than 25 °C, the fecundity of A. gossypii is inhibited [ 39 ]. In addition, host-specialized biotypes from different regions may differ in the degree of host specificity [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A single nymph per cage was monitored throughout the life cycle. Fitness parameters such as aphid survival (nymph to adult), nymphal period, adult period (pre-reproductive, reproductive, and post-reproductive), total fecundity, and intrinsic rate of increase were evaluated [ 37 , 38 ]. The total number of nymphs laid by an adult in the subsequent generation was recorded and removed from the cage.…”
Section: Methodsmentioning
confidence: 99%